Experimental and Theoretical Study of Effects of Varying Hydration on Elastic Properties and Microstructure of Shales and Sandstones - Yurikov, Alexey (Curtin University, 2018)
This thesis investigates how changing hydration affects elastic properties and microstructure of shales and sandstones. The experimental measurements show that adsorption of water causes elastic weakening and deformation of the rocks. The theoretical analysis of this data indicates driving mechanisms of these effects. One of them, a changing stiffness of compliant porosity, is responsible for drastic decrease of shear velocities in the rocks. The reported results can improve seismic and well log characterisation of reservoirs.